2002
DOI: 10.1083/jcb.200207008
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated kinase 4 interacts with integrin αvβ5 and regulates αvβ5-mediated cell migration

Abstract: p21-activated kinase 1 (PAK1) can affect cell migration (Price et al., 1998; del Pozo et al., 2000) and modulate myosin light chain kinase and LIM kinase, which are components of the cellular motility machinery (Edwards, D.C., L.C. Sanders, G.M. Bokoch, and G.N. Gill. 1999. Nature Cell Biol. 1:253–259; Sanders, L.C., F. Matsumura, G.M. Bokoch, and P. de Lanerolle. 1999. Science. 283:2083–2085). We here present a novel cell motility pathway by demonstrating that PAK4 directly interacts with an integrin intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 51 publications
11
85
1
Order By: Relevance
“…4f). These data are in agreement with our previous finding that PAK4 regulates breast cancer cell adhesion and migration on vitronectin, 11 indicating that PAK5 regulates integrin-mediated cell adhesion and migration in CRC cells.…”
Section: Pak5 Regulates Crc Cell Adhesion and Migrationsupporting
confidence: 83%
See 2 more Smart Citations
“…4f). These data are in agreement with our previous finding that PAK4 regulates breast cancer cell adhesion and migration on vitronectin, 11 indicating that PAK5 regulates integrin-mediated cell adhesion and migration in CRC cells.…”
Section: Pak5 Regulates Crc Cell Adhesion and Migrationsupporting
confidence: 83%
“…30,31 This process is major regulated by integrin and small GTPase Cdc42, and Rac1 whose targets are PAK family. [32][33][34][35] In our previous study, we found that PAK4 regulate integrin avb5-mediated breast carcinoma cell migration, 11 indicating that the Group B PAKs might be important to cell motility. Overexpression of PAK5 promoted formation of filopodia and neurite extension in N1E-115 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In further support, Pak family proteins have been implicated in integrin signaling. Upon integrin ␣ v ␤ 5 binding to vitronectin, Pak4 becomes colocalized with this integrin (37). Therefore, reduction or loss of ␤Pix expression might result in disruption to the paxillin/GIT/Pix/Pak complex at focal adhesions and therefore to a reduction in integrin signaling and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Migration assays were performed in Transwell migration chambers (pore size 8 mm; Costar, London, UK) essentially as described (Zhang et al, 2002). The lower compartment of the chambers contained 1 mg/ml high molecular weight HA (Sigma).…”
Section: Cell Migration Assaymentioning
confidence: 99%